Compressive yield stress of depletion gels from stationary centrifugation profiles. (4th January 2018) - Lattuada, Enrico; Buzzaccaro, Stefano; Piazza, Roberto
Abstract: We have investigated the stationary sedimentation profiles of colloidal gels obtained by an arrested phase-separation process driven by depletion forces, which have been compressed either by natural gravity or by a centrifugal acceleration ranging between 6 g and 2300 g . Our measurements show that the gel rheological properties display a drastic change when the gel particle volume fraction exceeds a value ϕ c, which barely depends on the strength of the interparticle attractive forces that consolidate the network. In particular, the gel compressive yield stress Π ( ϕ ), which increases as Π ( ϕ ) ∼ ϕ 4.2 for ϕ ≲ ϕ c, displays a diverging behaviour for ϕ > ϕ c, with an asymptotic value that is close to the random close packing value for hard spheres. The evidence we obtained suggests that ϕ c basically coincides with the liquid (colloid-rich) branch of the metastable coexistence curve, rather than with the lower (and ϕ -dependent) values expected for an attractive glass line penetrating inside the coexistence region.